Evaluation of the safety and efficacy of MonoMax® suture material for abdominal wall closure after primary midline laparotomy-a controlled prospective multicentre trial: ISSAAC [NCT005725079] - Albertsmeier, Markus; Seiler, Christoph; Fischer, Lars; Hüsing, Johannes; Büchler, Markus W. (Langenbeck's archives of surgery, 2011)
PURPOSE: Different suture techniques and various suture materials are in use to close midline incisions after primary laparotomy. The ISSAAC study aimed to assess the safety and efficacy of the new ultra-long-term absorbable, elastic monofilament suture material MonoMax® for abdominal wall closure. METHODS: This is a single-arm, multicentre prospective study that included 150 patients undergoing a primary elective midline incision. The control group consists of 141 patients from the INSECT study who received MonoPlus® or PDS® for abdominal wall closure. The incidences of burst abdomen and wound infection until the day of discharge were defined as the primary composite endpoints. The rate of incisional hernias 1 year after surgery, the length of postoperative hospital stay and safety parameters served as secondary endpoints. The study has been registered under www.clinicaltrials.gov [NCT005725079]. RESULTS: Eleven patients in the ISSAAC study [7.3%; 95% CI = (3.9; 13.1%)] experienced wound infection or burst abdomen until the day of discharge as compared to 16 [11.3%; 95% CI = (6.6; 17.8%)] patients in the INSECT control group (p = 0.31). The length of postoperative hospital stay was comparable in both study groups. One year after surgery, incisional hernias were observed in 21 ISSAAC patients (14.0%) in contrast to 30 hernias (21.3%) in the INSECT control group. CONCLUSIONS: The ultra-long-term absorbable, elastic monofilament suture material MonoMax® is safe and efficient for abdominal wall closure.
Gesehen am 17.04.2018